Analysis of Runway Utilization at Soekarno-Hatta Internasional Airport - ITL Trisakti*, ITL Trisakti, ITL Trisakti, ITL Trisakti , ITL Trisakti (International Journal of Advanced Science and Technology, 2020)
Long queues for the aircraft that will take-off, landing, and touch down show utilization (Level busyness) of runway at Soekarno-Hatta, are too high and lead to inefficiency, even direct and indirect losses to many parties. The purpose of research is:1) to calculate volume / traffic airplanes coming (landing), go (take-off), and touch down2) calculate the average queuing length of aircraft and spend time for queuing using the runway. The method of research is using Queuing Theory. The results showed an average aircraft movements 46.41 aircraft / hour, the average capacity of service runway is 36 aircraft / hour / runway, utilization of 2 runway is ρ = 64.46, the average time aircraft queue that'll take off, landing, and touch down is 1.79 minutes; the average number of queues to wait to use a runway that'll take off, landing, and will touch down using 2 runway is 2.67aircrafts.